IDENTIFIKASI SENYAWA BIOAKTIF DARI BUBUK DAUN CAKAR AYAM (Selaginella spp.) KOMERSIAL DAN EKSTRAKNYA MENGGUNAKAN METODE FTIR - Witoyo, Jatmiko Eko; Utoro, Panggulu Ahmad Ramadhani; Maligan, Jaya Mahar (Universitas Muhammadiyah Semarang, 2024)
Increased public awareness of the back-to-nature lifestyle has encouraged using natural materials, especially for health purposes. One of the natural ingredients that attracts attention and has the potential to be developed is Selaginella spp. leaves, commonly known as